Onychomycosis due to Candida parapsilosis in a Child with Ventricular Septal Defect: An Unusual Predisposition - Supram Hosuru Subramanya; Deependra Hamal; Niranjan Nayak; Shishir Gokhale (Hindawi Limited, 2016)
Candida parapsilosis is emerging as a potential pathogen for onychomycosis. A 4-year-old male child with perimembranous ventricular septal defect (VSD) was admitted with features of cystitis and was treated with broad spectrum antibiotics. Two weeks later, he developed yellowish discoloration of nails of both hands. The sloughed out nail, on microscopy, showed numerous yeast forms that were identified as Candida parapsilosis by both phenotypic and genotypic methods. Antifungal sensitivity testing of the isolate was performed by microbroth dilution method in accordance with CLSI guidelines. Patient was successfully treated with topical amphotericin B and oral fluconazole. Thus, one should have a high index of suspicion of C. parapsilosis onychomycosis, especially when the patient is in the paediatric age group, presenting with unusual predisposing condition like congenital heart disease, and is on broad spectrum antibiotics.